2007
DOI: 10.1016/j.bcp.2006.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of human estrogen sulfotransferase (hSULT1E1)

Abstract: Sulfotransferases (SULTs) are enzymes that catalyze the sulfation of hydroxyl-containing compounds. Sulfation regulates hormone activities and detoxifies xenobiotics. Human estrogen sulfotransferase (hSULT1E1) catalyzes the sulfation of estrogens and regulates estrogen bioactivities. Oxidative regulation provides a biological mechanism for regulating enzyme activities in vivo. The oxidative regulation of human SULTs has not been reported. In this study, we used amino acid modification, manipulation of intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
7
28
1
Order By: Relevance
“…Oxidative regulation of the catalytic activity of cytosolic sulfotransferases has been demonstrated in family 1 SULTs, including members of both SULT1A, as well as SULT1E subfamilies (Marshall et al, 1997;Maiti et al, 2005Maiti et al, , 2007. Our results from the present study indicate that the catalytic activity of hSULT2A1, an important member of the SULT2 family in humans, can also be modulated through oxidation at cysteine residues.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Oxidative regulation of the catalytic activity of cytosolic sulfotransferases has been demonstrated in family 1 SULTs, including members of both SULT1A, as well as SULT1E subfamilies (Marshall et al, 1997;Maiti et al, 2005Maiti et al, , 2007. Our results from the present study indicate that the catalytic activity of hSULT2A1, an important member of the SULT2 family in humans, can also be modulated through oxidation at cysteine residues.…”
Section: Discussionsupporting
confidence: 61%
“…Since the reversibility of oxidative modification of family 1 SULTs has been previously demonstrated (Maiti et al, 2007), we sought to determine the reversibility of disulfide bond formation in hSULT2A1. Following a 1-hour treatment of hSULT2A1 with 0.5 mM diamide or 0.5 mM Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triclosan was purchased from Merck (Darmstadt, Germany). Rabbit anti-human EST antibody (for the Western blot assay) [32] was a gift from Dr David RINGER (American Cancer Society) [21] . The peptide antigen sequence used for generating this antibody is NH 2 -(Glu-Gln-Gln-Met-Lys-Glu-SerThr-Leu-Lys-Phe-Arg-Thr-Glu-ILe) [33] .…”
Section: Methodsmentioning
confidence: 99%
“…Although this was first described for purified rSULT1A1 (Marshall et al, 1997), investigations of cytosolic and purified preparations of human estrogen sulfotransferase, hSULT1E1, have indicated that the catalytic function of this SULT also can be altered by treatment with GSSG (Maiti et al, 2007). In addition, studies with rats continuously exposed to hyperoxic condi- tions (i.e., Ͼ95% oxygen) showed that there was an increase in the rate of sulfation of 2-naphthol catalyzed by subsequently isolated hepatic and lung cytosolic fractions (Maiti et al, 2005).…”
Section: Discussionmentioning
confidence: 99%